MOTIF PENGGUNAAN PAY LATER PADA WANITA KARIR KOTA SURABAYA (The Commercium, 2023)
Today, technology is developing rapidly and all of society's needs can be easily met. One of the most popular payment methods today, especially among career women, is Pay later. Therefore, it is interesting to examine the "Motives for Using Pay Later among Career Women in Surabaya City". The purpose of this study is to describe the dominant motives and reasons for women using Pay Later among career women in Surabaya City. The method used in this research is a qualitative approach with descriptive nature. The data collection technique used snowball sampling. To obtain information, researchers used in-depth interview techniques with 6 informants who are career women in Surabaya City. This research uses Alfred Schutz's theory, which explains that there are two categories of motives or motivations: in order to motive and because of motive. The results of this study indicate that the motives for using Pay Later among career women in Surabaya City from 6 informants are (1) ease of transactions, (2) encouragement from colleagues, (3) effective time, (4) many attractive offers, (5) can make installments and (6) can save cash. Although the consequences or consequences that can be caused are (1) becoming consumptive, (2) the desire to stop due to various negative causes arising from this use, (3) and excessive use and can trigger various problems